Vibro-oscillatory therapy in the rehabilitation of respiratory function in person with pulmonary atelectasis: Case Report - Sérgio Vaz; Ana Sofia Loureiro; Ana Sofia Vilela; Jacinta Martins; Andreia Félix; André Novo (Associação Portuguesa dos Enfermeiros de Reabilitação, 2022)
Introduction: A person with pulmonary atelectasis can present significant changes in respiratory function, and a specialized rehabilitation intervention is essential to enhance the person's quality of life, optimize respiratory function, enable the person and respiratory symptom management. Objective: Evaluate the sensible gains of rehabilitation nursing care in optimizing the respiratory function of a person with a clinical diagnosis of pulmonary atelectasis using vibro-oscillatory therapy. Methodology: Descriptive case report study prepared in accordance with the guidelines of the CAse REports. Applied the nursing process using the Documentary Standard of Care of the Rehabilitation Nursing Specialty. A 73-year-old male, admitted to the pulmonology service with impaired respiratory function and impaired sputum capacity. Results: With the implementation of the Rehabilitation Nursing intervention program, gains were evidenced in the reduction of dyspnea, culminating in the person's discharge and reintegration into community. Conclusion: With the systematization and implementation of an individualized rehabilitation nursing care plan, it's possible to record the effectiveness of interventions in controlling and reducing the person's dyspnea.